Effect of miRNAs, Proinflammatory Cytokines and ACE2 in COVID-19 Pathophysiology - Singh, Hari O.; Jakhar, Kamini; Nema, Vijay; Krishnaraj, Asha; Choudhari, Ranjana (Coronaviruses, 2021)
Background: Angiotensin-converting enzyme 2 (ACE2) is the main cellular receptor for the entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and acts as a pro-inflammatory mediator of Coronavirus disease (COVID-19). The clinical outcome of SARS-CoV-2 infection is influenced by the pro-inflammatory mediators. The specific microRNAs (miRNAs) influence the ACE2 expression and are accountable for the increased circulatory pro-inflammatory mediator levels. Thus, host factors play a crucial role in COVID-19 pathophysiology. The pathogenesis of COVID-19 disease is not well understood. Hence we comprehended the role of miRNAs, pro-inflammatory cytokines, and ACE2 genes in COVID-19 pathophysiology. Methods: We utilized multiple databases, specifically EMBASE, PubMed (Medline), and Google Scholar, for our search. Discussion: SARS-CoV-2 genes could be the target of host miRNAs. The miRNAs regulate the expression of ACE2 in various organs, including the kidney, heart, blood vessels, and lung. ACE2 acts as a pro-inflammatory mediator of SARS-CoV-2 associated disease. Pro-inflammatory cytokines (IL-6, IL-1β, and TNF) have been associated with severe COVID-19 disease. Hence variation in expression of miRNAs would influence the regulation of COVID-19 pathophysiology. The clinical outcomes of COVID-19 are variable which could be linked with the difference in binding of host miRNA to the target genes. Conclusion: Correlation of these genes with severe or critical stages of patients will provide biomarkers for the severity of lung inflammation which would be useful in the rapid identification of patients in need of hospital admission. Analysis of the relationship between the miRNAs and ACE2 will be helpful in designing anti-miR therapy for ACE2-related SARS-CoV-2 infection.
Keywords: pro-inflammatory cytokines